2011
DOI: 10.1634/theoncologist.2011-0039
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Prognostic Model in Patients with Oxaliplatin-Based or Irinotecan-Based First-Line Chemotherapy for Metastatic Colorectal Cancer: A GERCOR Study

Abstract: received from Genentech, Bristol-Myers Squibb, and Pfizer; and ownership interest with Tetralogic Pharmaceuticals. Reviewer "A" discloses no financial relationships. The content of this article has been reviewed by independent peer reviewers to ensure that it is balanced, objective, and free from commercial bias. On the basis of disclosed information, all conflicts of interest have been resolved. LEARNING OBJECTIVESAfter completing this course, the reader will be able to:1. Describe prognostic factors in metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 44 publications
3
49
0
1
Order By: Relevance
“…Another limitation of our study is the absence of PAL recording in the "cohort set-2." Nevertheless, we did not observe any association between PAL and Ang-2 in the "cohort set-1" Moreover, the GERCOR analysis, performed on 803 patients mCRC treated by FOLFOX or FOLFIRI in the first-line setting demonstrated that LDH, number of metastatic sites, and PS were the only independent prognostic factors (24).…”
Section: Cancer Epidemiol Biomarkers Prev; 24(3) March 2015mentioning
confidence: 57%
See 2 more Smart Citations
“…Another limitation of our study is the absence of PAL recording in the "cohort set-2." Nevertheless, we did not observe any association between PAL and Ang-2 in the "cohort set-1" Moreover, the GERCOR analysis, performed on 803 patients mCRC treated by FOLFOX or FOLFIRI in the first-line setting demonstrated that LDH, number of metastatic sites, and PS were the only independent prognostic factors (24).…”
Section: Cancer Epidemiol Biomarkers Prev; 24(3) March 2015mentioning
confidence: 57%
“…However, the GERCOR score displayed a better discriminative ability (C ¼ 0.64) than the Kohne model (C ¼ 0.55; ref. 24). We then used the GERCOR model as the reference score.…”
Section: Added Value Of the Ang-2 Parameter For Predicting Osmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of baseline laboratory data were evaluated in prospective chemotherapy studies and found to predict treatment outcome including: elevated lactate dehydrogenase (LDH) (14,15), white blood cell J Gastrointest Oncol 2017;8(1):70-80 jgo.amegroups.com Table 3 Summary of significant differences in the reporting of all grades and severe (CTCAE grade ≥3) all-causality adverse events over day 0-90 from first RE procedure in A.…”
Section: Pre-treatment Liver Dysfunction Affects Outcomes After Rementioning
confidence: 99%
“…Наибольшее время без ХТ было отмечено в группе пациентов с хорошим соматическим статусом (ECOG -0-1), низким уровнем лактатдегидрогеназы (ЛДГ) и щелочной фосфатазы (≤ 3 верхним границам нормы), небольшой распространенностью опухолевого процесса (≤ 1 органа, пораженного метастазами) [2]. Отметим, что в качестве факторов неблагоприят-ного прогноза при совокупном анализе данных 3 ис-следований -OPTIMOX1 (сравнение схемы FOLFOX4 до прогрессирования и интермитирующей ХТ по схеме FOLFOX7) [3], OPTIMOX2 и C97-3 (схемы FOLFIRI в 1-й линии и FOLFOX6 во 2-й против обратной по-следовательности) -были выделены следующие при-знаки неблагоприятного прогноза: низкий соматичес-кий статус (ECOG 2), высокий уровень ЛДГ (> 1 верхней границы нормы), поражение метастазами > 1 органа [4]. Также при анализе исследований OPTIMOX1 и OPTI-MOX2 было выявлено, что пациенты с нормальным уровнем РЭА выигрывали от «ХТ-каникул» по сравне-нию с больными, которым продолжали ХТ до прогрес-сирования [5].…”
Section: рис 1 выживаемость без прогрессированияunclassified